PENGARUH IMPLEMENTASI KEBIJAKAN PEMERINTAH DAERAH TERHADAP EFEKTIVITAS PERUBAHAN JARINGAN TRAYEK ANGKUTAN UMUM DI KABUPATEN CIANJUR - Ayu Ayda Lestari; Toto Kushartono; Arlan Siddha (Jurnal Caraka Prabu, 2020)
The title of this research is : "The Effect of Local Government Policy Implementation on the Effectiveness of Changes in the Public Transportation Route Network in Cianjur Regency". The background of this research is the ineffective implementation of local government policy. This research used an explanation survey with a quantitative approach. This research was conducted at the Cianjur Regency Transportation Service Office, Rawabango Terminal, Pasirhayam Terminal, Main Market, Jalan Siliwangi, Jalan Dr. Muwardi. Collecting data in this research is through survey, observation, and documentation. The sampling technique used is probability sampling with simple random sampling. The theory of this research is policy implementation from Mazmanian and Sabartier and for the theory of effectiveness by Siagian. The results of the research showed that there is no affect of the implementation of local government policy on the effectiveness of changes in the network of public transport routes in Cianjur Regency. Marked by the characteristics of the problem can not be identified, then the carrying capacity of regulations and non-regulations that can affect the process of implementation can not be implemented properly.